PENGELOLAAN PERIKANAN LOBSTER (Panulirus sp.) DENGAN METODE ECOSYSTEM APPROACH TO FISHERIES MANAGEMENT DI KABUPATEN SIMEULUE - Roni Arif Munandar; M Ali Sarong; Edwarsyah Edwarsyah (Universitas Teuku Umar, 2018)
Management of lobster fisheries aims to analyze lobster fisheries management system and lobster resource management pattern through Ecosystem Approach to Fisheries Management (EAFM) at the Simeulue Regency Aceh Province. The study was conducted in a lobster breeding area, at the sub-district of South Teupah and sub-district of Teluk Dalam Simeulue regency in June to July 2016, location determination using purposive sampling method. Data collection with questionnaires and direct field-taking. Analysis of data processing using analysis of fisheries management indicators through ecosystem approach (EAFM). The results showed that assessment indicator EAFM for fish resource domains in good condition (220), habitat and ecosystem domains in good condition (205), and institutional domains are also in good condition (227).Keywords: EAFM, Ecosystems, Lobsters, Simeulue